Targeted optical fluorescence imaging: a meta-narrative review and future perspectives. - Schouw, H. M.; Huisman, L. A.; Janssen, Y. F.; Slart, R. H. J. A.; Borra, R. J. H.; Willemsen, A. T. M.; Brouwers, A. H.; van Dijl, J. M.; Dierckx, R. A.; van Dam, G. M.; Szymanski, W.; Boersma, H. H.; et al. (European Journal of Nuclear Medicine & Molecular Imaging, 2021)
Purpose: The aim of this review is to give an overview of the current status of targeted optical fluorescence imaging in the field of oncology, cardiovascular, infectious and inflammatory diseases to further promote clinical translation. Methods: A meta-narrative approach was taken to systematically describe the relevant literature. Consecutively, each field was assigned a developmental stage regarding the clinical implementation of optical fluorescence imaging. Results: Optical fluorescence imaging is leaning towards clinical implementation in gastrointestinal and head and neck cancers, closely followed by pulmonary, neuro, breast and gynaecological oncology. In cardiovascular and infectious disease, optical imaging is in a less advanced/proof of concept stage. Conclusion: Targeted optical fluorescence imaging is rapidly evolving and expanding into the clinic, especially in the field of oncology. However, the imaging modality still has to overcome some major challenges before it can be part of the standard of care in the clinic, such as the provision of pivotal trial data. Intensive multidisciplinary (pre-)clinical joined forces are essential to overcome the delivery of such compelling phase III registration trial data and subsequent regulatory approval and reimbursement hurdles to advance clinical implementation of targeted optical fluorescence imaging as part of standard practice.